AERODYNAMIC PERFORMANCE ANALYSIS BY ADDING U-GROOVE RIBLETS ON FLAPS WITH NACA 43018 AIRFOIL - Lefrant Tonapa, Juanda; Hariyadi, Setyo; Irfansyah, ade (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
At this time NACA 43018 airfoil is only used on the wing of ATR 72 aircraft both 500 and 600 series. With the addition of U-groove riblets on NACA 43018 airfoil is expected to be used in other aircraft. Because with the addition of Ugroove riblets that can increase the coefficient of lift and decrease the coefficient of drag so that it can increase the performance of the airfoil. with good airfoil performance it will save fuel for the aircraft and can delay separation. In this study, the analysis of aerodynamic characteristics on the airfoil was carried out by simulating the air on the test object in the form of NACA 43018 airfoil geometry which was given an extension in the form of riblets with variations in the shape of u-groove and slotted wing. The software used is ANSYS R22. Data processing using the Computational Fluid Dynamic (CFD) method.The results of this study are as follows , and / The results of this study show that the addition of U-groove riblets helps improve the aerodynamic performance of the NACA 43018 airfoil flap. With an average percentage increase of all angles of attack given is 2% and the average percentage of decrease of all angles of attack given is 9%